2022
DOI: 10.18196/jbti.v13i3.17538
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Compensation Moderates Individual Factors towards Employee Performance at XXX Palembang Company

Abstract: This study aims to determine the effect of work discipline, appreciation, motivation and responsibility on performance. The number of respondents to the research was 66 people, the sampling technique was by applying saturation sampling. The data used is primary data, namely by questionnaire and secondary data. Exogenous variables consist of work discipline, motivation, protection as well as moderating variables while endogenous variables are employee performance. The scale of measurement of indicator variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…This makes compensation one of important determinants of organisational performance. The findings are consistent with those of Cahyani et al (2022); Kayani and Gan (2022) and Kim and Jang (2020). Given unsatisfactory performance of many public organisations in Tanzania, these findings call for the government to assess and rethink about compensations that public servants receive.…”
Section: Discussion Of Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This makes compensation one of important determinants of organisational performance. The findings are consistent with those of Cahyani et al (2022); Kayani and Gan (2022) and Kim and Jang (2020). Given unsatisfactory performance of many public organisations in Tanzania, these findings call for the government to assess and rethink about compensations that public servants receive.…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…Organisations that offer better compensation packages tend to possess a higher probability to do better compared to those whose packages are considered unattractive. Compensation practices are linked to their ability to motivate people and therefore instill the spirit to work better and happily which are crucial to organisational performance (Cahyani et al, 2022). The study of Kayani and Gan (2022) which was done among Asia Pacific firms found increased pay of CEO resulted to boosted performance of firms.…”
Section: Compensation and Organisational Performancementioning
confidence: 99%